Exploring the genetics of lesion and nodal resistance in pea (Pisum sativum L.) to Sclerotinia sclerotiorum using genome‐wide association studies and RNA‐Seq. (26th June 2018) - Chang, Hao‐Xun; Sang, Hyunkyu; Wang, Jie; McPhee, Kevin E.; Zhuang, Xiaofeng; Porter, Lyndon D.; Chilvers, Martin I.
Abstract: The disease white mold caused by the fungus Sclerotinia sclerotiorum is a significant threat to pea production, and improved resistance to this disease is needed. Nodal resistance in plants is a phenomenon where a fungal infection is prevented from passing through a node, and the infection is limited to an internode region. Nodal resistance has been observed in some pathosystems such as the pea ( Pisum sativum L.)‐ S. sclerotiorum pathosystem. In addition to nodal resistance, different pea lines display different levels of stem lesion size restriction, referred to as lesion resistance. It is unclear whether the genetics of lesion resistance and nodal resistance are identical or different. This study applied genome‐wide association studies (GWAS) and RNA‐Seq to understand the genetic makeup of these two types of resistance. The time series RNA‐Seq experiment consisted of two pea lines (the susceptible 'Lifter' and the partially resistant PI 240515), two treatments (mock inoculated samples and S. sclerotiorum ‐inoculated samples), and three time points (12, 24, and 48 hr post inoculation). Integrated results from GWAS and RNA‐Seq analyses identified different redox‐related transcripts for lesion and nodal resistances. A transcript encoding a glutathione S‐transferase was the only shared resistance variant for both phenotypes. There were more leucine rich‐repeat containing transcripts found for lesion resistance, while different candidate resistance transcripts such as a VQ motif‐containing protein and a myo‐inositol oxygenase were found for nodal resistance. This study demonstrated the robustness of combining GWAS and RNA‐Seq for identifying white mold resistance in pea, and results suggest different genetics underlying lesion and nodal resistance.